2013
DOI: 10.1111/fme.12028
|View full text |Cite
|
Sign up to set email alerts
|

Feeding strategy of the non‐native rainbow trout,Oncorhynchus mykiss, in low‐orderPatagonian streams

Abstract: The dietary composition and feeding strategy of rainbow trout, Oncorhynchus mykiss (Walbaum), in two low‐order Patagonian streams were studied. Benthic macroinvertebrate availability was estimated in both riffles and pools. Fish stomach contents were examined to determine prey richness and diversity, prey electivity, food‐niche width, and the feeding strategy employed by trout throughout the year. Availability of benthos varied seasonally with Ephemeroptera, Trichoptera, Plecoptera and Diptera species dominati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
3
11
0
4
Order By: Relevance
“…As in other studies in southern South America, the diet of Rainbow Trout consists mainly of benthic aquatic macroinvertebrates and a few terrestrial taxa, confirming the generalist-opportunist diet of this species in southern Chile (Arismendi et al, 2012;Di Prinzio et al, 2013;Vargas-Chacoff et al, 2013). The response of Rainbow Trout to food availability in this study, suggest that the diet is influenced by the type of riparian vegetation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As in other studies in southern South America, the diet of Rainbow Trout consists mainly of benthic aquatic macroinvertebrates and a few terrestrial taxa, confirming the generalist-opportunist diet of this species in southern Chile (Arismendi et al, 2012;Di Prinzio et al, 2013;Vargas-Chacoff et al, 2013). The response of Rainbow Trout to food availability in this study, suggest that the diet is influenced by the type of riparian vegetation.…”
Section: Discussionsupporting
confidence: 85%
“…Like other salmonids in the region, Rainbow Trout is known as generalist and largely opportunistic feeder (e.g., Arenas, 1978;Campos et al, 1984;Ruiz, 1993;Berrios et al, 2002;Palma et al, 2012;Arismendi et al, 2012;Vargas-Chacoff et al, 2013). Most of these studies have related the diet of Rainbow Trout with the availability of macroinvertebrates in the environment in summer, but few of them have investigated this across seasons (Buria et al, 2009;Di Prinzio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and width of the rainbow trout diet observed in this study is similar to that reported for this Table 3 Selectivity index (Ivlev) of prey in the diet of rainbow trout (Oncorhynchus mykiss) (Arismendi et al 2012;Di Prinzio et al 2013) but higher than the observed in the native catfish Hatcheria macraei (Ferriz 1994(Ferriz , 2012Barriga et al 2009;Di Prinzio and Casaux 2012). This fact supports the proposal by Di Prinzio et al (2013) indicating that the expansion success of the rainbow trout in Patagonia could be explained, among other factors, by their high feeding plasticity, which depends on different issues (prey-type characteristics, seasonal changes in resource supply, food-habitat utilization, etc.). This allows the trout to exploit temporarily abundant food resources and switch between specialized and generalized feeding strategies, buffering changes in food availability as observed in some streams in Patagonia (Di Prinzio et al 2013).…”
Section: Discussionsupporting
confidence: 85%
“…These preys contributed strongly to the diet in late summer and early autumn in NyF and in late spring and summer in CVA, decreasing their importance as prey in the remaining seasons. Despite of the overall dominance of these species, the composition of the diet varied seasonally as observed in previous studies carried out in the region (Buria et al 2009;Di Prinzio and Casaux 2012;Di Prinzio et al 2013). Rainbow trouts from both streams tended to forage on the larger individuals of each prey species.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation